Transtornos mentais maternos graves e risco de malformação congênita do bebê: uma metanálise Severe mental illness in mothers and congenital malformations in newborns: a meta-analysis - Priscila Krauss Pereira; Lúcia Abelha Lima; Mônica Maria Ferreira Magnanini; Leticia Fortes Legay; Giovanni Marcos Lovisi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
O risco de ter malformações parece ser maior em bebês de mães com transtornos mentais em comparação com bebês de mães sem histórico de transtornos psiquiátricos. O objetivo deste artigo foi realizar uma metanálise dos estudos sobre a associação entre transtornos mentais maternos e malformações congênitas. A revisão consistiu na busca de artigos nas bases MEDLINE, ISIWEB, Scopus, LILACS e SciELO, utilizando-se os descritores: "mental disorders" OR "mental health" OR "psychotic disorders" OR "schizophrenia" AND "congenital abnormalities" OR "birth defects". Foram localizados 108 estudos, sendo selecionados cinco artigos de acordo com os critérios estabelecidos. Estes artigos foram incluídos na metanálise, envolvendo um total de 4.194 crianças de mães com transtornos mentais e 249.548 crianças de mães sem tais transtornos. A medida combinada revelou associação significativa entre exposição a transtornos mentais maternos e risco de malformações (RR = 2,06, IC95%: 1,46-2,67). O presente estudo evidencia a relação entre saúde mental materna durante a gravidez e suas repercussões na saúde do bebê. The risk of congenital malformations appears to be higher in infants of mothers with mental disorders as compared to those of mothers with no history of psychiatric illness. This article presents a meta-analysis of studies on the association between maternal mental illness and congenital malformations. The review consisted of an article search in the MEDLINE, ISIWEB, Scopus, and SciELO databases, using the following key words: "mental disorders" OR "mental health" OR "psychotic disorders" OR "schizophrenia" AND "congenital abnormalities" OR "birth defects". A total of 108 studies were identified, and five articles were selected according to the established criteria. These articles were included in a meta-analysis, involving a total of 4,194 children of mothers with mental illness and 249,548 children of mothers with no such disorders. Pooled relative risk showed a significant association between exposure to mental illness in mothers and risk of malformations in newborns (RR = 2.06, 95%CI: 1.46-2.67). The study highlights the relationship between maternal mental health during pregnancy and its effects on the infant's health.